N-acetylcysteine attenuates endotoxin-induced leukocyte-endothelial cell adhesion and macromolecular leakage in vivo - Schmidt, Heinfried; Schmidt, Werner; Müller, Thomas; Böhrer, Hubert; Gebhard, Martha-Maria; Martin, Eike (Critical care medicine, 1997)
Measurements and Main Results Leukocyte adherence, red cell velocity (VRBC), vessel diameters, venular wall shear rate, and macromolecular leakage were determined in mesenteric postcapillary venules using in vivo videomicroscopy at baseline and at 30, 60, 90, and 120 mins after the start of the endotoxin challenge. Endotoxin exposure induced a marked increase in adherent leukocytes (group B: baseline, 391 +/- 24 cells/mm2; 120 mins, 1268 +/- 131 cells/mm2; p < .01). N-acetylcysteine pretreatment attenuated the adherence of leukocytes during endotoxemia (baseline, 366 +/- 28 cells/mm2; 120 mins, 636 +/- 49 cells/mm2; p < .01 vs. baseline; p < .01 vs. group B). Leukocyte adherence in control animals (group C) did not increase significantly. Administration of N-acetylcysteine did not influence the decrease in VRBC observed during endotoxemia. In group B, VRBC decreased during the infusion of endotoxin from 2.0 +/- 0.2 mm/sec at baseline to 1.1 +/- 0.2 mm/sec after 120 mins (p < .01 vs. baseline; p < .05 vs. group C), and in group A from 2.2 +/- 0.2 mm/sec to 1.1 +/- 0.1 mm/sec after 120 mins (p < .01 vs. baseline; p < .05 vs. group C). In group C, VRBC remained unchanged (baseline, 1.7 +/- 0.2 mm/sec; at 120 mins, 1.5 +/- 0.2 mm/sec). The venular diameters remained unchanged in all groups during the entire study period. After 120 mins, the venular wall shear rate decreased from 502 +/- 62 secs sup -1 at baseline to 272 +/- 46 sec sup -1 in group B (p < .01), and from 563 +/- 45 secs sup -1 at baseline to 283 +/- 31 secs sup -1 in group A (p < .01). No differences in venular wall shear rate were observed between these groups. In group C, the venular wall shear rate remained unchanged (baseline, 457 +/- 54 secs sup -1; at 120 mins, 409 +/- 51 secs sup -1). Macromolecular leakage, expressed as perivenular/intravenular fluorescence intensity after injection of fluorescence-labeled albumin, increased from 0.29 +/- 0.03 to 0.58 +/- 0.03 (p < .01) during the infusion of endotoxin in group B. In contrast, pretreatment with N-acetylcysteine diminished the extravasation of albumin (baseline, 0.27 +/- 0.01; at 120 mins, 0.37 +/- 0.02; p < .01 vs. baseline; p < .01 vs. group B). - Conclusion - These results demonstrate that N-acetylcysteine attenuates endotoxin-induced alterations in leukocyte-endothelial cell adhesion and macromolecular leakage, suggesting N-acetylcysteine might be therapeutic in the prevention of endothelial damage in sepsis. (Crit Care Med 1997; 25:858-863)
Gesehen am 29.04.2024